Disseminated tumour cells in bone marrow in experimental colon cancer: metastatic or resident?. (24th June 2013) - Barone, M.; Altomare, D. F.; Rotelli, M. T.; Scavo, M. P.; Piscitelli, D.; De, N.; Bocale, D.; Di Leo, A.
Abstract Aim There are conflicting data on the biological and prognostic significance of disseminated tumour cells (DTCs) in the bone marrow of colorectal cancer patients since bone metastasis is rare in this disease. The study aimed to determine the origin of bone marrow DTCs using human colorectal cancer cells in in vivo and in vitro experimental settings. Method CD1 nude female mice were xenotransplanted with SW620 cells (a colorectal cancer cell line isolated from a male patient) injected in the colon wall. At autopsy, the presence of SW620 in the bone marrow (BM), colon and other organs/tissues was recognized by detection of the epithelial marker cytokeratin‐19 (CK19) and Y chromosome. In addition SW620 cells or their conditioned medium were cultured with human BM cells. Results Macroscopically evident CK19+/Y‐chromosome‐positive tumours developed only in five mice receiving SW620 cells while putative DTCs (CK19+) were found in the bone marrow of all treated mice. Most of these CK19+ cells were Y chromosome negative, only few being Y chromosome positive. In vitro SW620 cells or their conditioned medium induced CK19 expression in cultured human bone marrow cells. Conclusion Experimental colorectal cancer can induce the appearance of two distinct CK19+ cell populations in the bone marrow, one of metastatic origin and the other of murine origin. These findings suggest that bone marrow cells may undergo phenotypic modifications induced by cancer cells.